Creativity training in causal inference using the idea post-exposure paradigm: Effects on idea generation in junior high school students. (December 2016) - Sannomiya, Machiko; Yamaguchi, Yosuke
Highlights: The effect of a creativity training in causal inference was investigated. A repeated IPE (idea post-exposure) paradigm was effective. The training enhanced fluency and flexibility of idea generation. The training improved metacognitive beliefs about creative thinking. The training enhanced motivation for creative thinking. Abstract: In the present study, an experiment was performed to examine the effects of training in creative causal inference using a repeated idea post-exposure (IPE) paradigm on the ability of junior high school students to generate ideas. The essential components of the training were as follows: 1) repeated practice in causal inference, 2) post exposure to others' ideas, and 3) the use of various everyday problems. The results showed that participants in the training condition exhibited a general increase in the number of ideas and their categories. Their ratings revealed that they explicitly recognized the effect of training on their idea generation and attitudes about thinking. They positively evaluated the aforementioned three essential components. They also reported that improvements in their ability and persistence in idea generation through this training, which suggests that they acquired the metacognitive belief that creative thinking ability can be enhanced with training. Future work should examine the effects of IPE and repeated practice separately, and how training is affected by the quantity and quality of the ideas to which participants are exposed.